P64 flow diverter: Results in 108 patients from a single center. Issue 1 (February 2021) - De Beule, Tom; Boulanger, T; Heye, S; van Rooij, WJ; van Zwam, WH; Stockx, L
Background and purpose: Flow diverters are increasingly used to treat intracranial aneurysms. We report the safety and efficacy of the p64 flow diverter, a resheathable and detachable device for intracranial aneurysms. Materials and methods: We retrospectively reviewed 108 patients with 109 aneurysms treated with the p64 between March 2014 and July 2019. There were 87 women and 21 men, mean age 57 years. Of 109 aneurysms, 74 were discovered incidentally, 12 were symptomatic, 18 were previously treated, and five were ruptured dissection aneurysms. A total of 10 aneurysms were located in the posterior circulation. The mean aneurysm or remnant size was 8.1 mm. Results: Hemorrhage by perforation with the distal guidewire occurred in two patients with permanent neurological deficits in one. In one patient, acute in-stent occlusion caused infarction with a permanent deficit. Permanent morbidity was 1.9% (2 of 108, 95%CI 0.1–6.9%); there was no mortality. During follow-up, three in-stent occlusions occurred, all asymptomatic. There were no delayed hemorrhagic complications. At six months, 77 of 96 aneurysms (80.2%) were completely occluded, and at last follow-up, this increased to 93 of 96 aneurysms (96.9%). In-stent stenosis at any degree occurred in 11 patients, progressing to asymptomatic complete occlusion in one. In the other patients, stenosis resolved or improved at further follow-up. Conclusion: The p64 offers an effective and safe treatment option. Aneurysm occlusion rate was 97% at last follow-up, mostly achieved with a single device. There were no delayed hemorrhagic complications. Delayed in-stent stenosis infrequently progresses to occlusion but remains a matter of concern.